Consumption and the literary cookbook - Wesselius, Janet Catherina; Harde, Roxanne (Routledge, 2021)
"Combining cultural and literary studies approaches to literary cookbooks and the narratives surrounding them, this book offers intelligent and entertaining readings focused on rhetorical and gastronomical consumption"--